Pemodelan variasi weight roller CVT terhadap torsi mesin K20 menggunakan metode logika Fuzzy - Reinaldi Teguh Setyawan; Gunawan Gunawan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
This research was conducted to find the gray value of the Weight roller weight test against the engine RPM of a motorized vehicle, torque is the desired result. Large torque but still within reasonable limits of fuel use, namely 1:15. After testing using the Dyno test, the results are processed using fuzzy logic. The use of weight rollers is indeed proven to be able to increase the torque value of a machine, but the results can change depending on the processed value, therefore it is assisted by a fuzzy system to get maximum results. The use of a 13 gr weight roller produces a torque of 08.89 Nm at 5000 RPM which is smaller than the torque on a standard size Weight Roller which is 10 gr.